(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Caudal epidural block is a commonly used regional anesthetic technique for anorectal surgeries because it provides effective intraoperative anesthesia and postoperative analgesia with minimal hemodynamic disturbances. Addition of adjuvants such as ketamine to local anesthetic agents may improve the quality and duration of analgesia. The present study was conducted to compare the effectiveness of caudal block using lignocaine alone and lignocaine combined with ketamine in adults undergoing anorectal surgeries. Methodology: This prospective randomized comparative study was conducted in the Department of Anaesthesiology at Sree Mookambika Institute of Medical Sciences from June 2025 to March 2026. Fifty patients aged between 20 and 60 years belonging to ASA Grade I and II undergoing anorectal surgeries were included in the study. Patients were randomly allocated into two groups of25 each. Group C received 30 ml of 1.5% lignocaine for caudal block, whereas Group T received 30 ml of 1.5% lignocaine combined with ketamine 0.5 mg/kg. Parameters assessed included onset of anesthesia, time to start surgery, sensory dermatome level, motor blockade, positional pain score, patient satisfaction, and surgeon satisfaction. Statistical analysis was performed using Student’s t-test and Chi-square test, with p-value <0.05 considered statistically significant. Results: The onset of anesthesia was significantly faster in Group T (5.16 ± 1.75 minutes) compared to Group C (6.04 ± 1.51 minutes) with p=0.045. Mean time to start surgery was significantly shorter in Group T (10.48 ± 1.64 minutes) than Group C (11.44 ± 1.83 minutes) with p=0.008. Group T demonstrated higher sensory dermatome levels at 5, 10, and 15 minutes compared with Group C. Positional pain score was lower in Group T, while patient and surgeon satisfaction scores were significantly higher in the ketamine group. Conclusion: Addition of ketamine to lignocaine in caudal epidural block provided faster onset of anesthesia, improved sensory blockade, better analgesia, and greater patient and surgeon satisfaction compared with lignocaine alone in adult anorectal surgeries.